2013
DOI: 10.1136/heartjnl-2013-304958
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary predictors of death and sustained ventricular tachycardia in patients with repaired tetralogy of Fallot enrolled in the INDICATOR cohort

Abstract: ObjectivePatients with repaired tetralogy of Fallot (TOF) experience increased rates of mortality and morbidity in adulthood. This study was designed to identify risk factors for death and ventricular tachycardia (VT) in a large contemporary cohort of patients with repaired TOF.MethodsSubjects with repaired TOF from four large congenital heart centres in the USA, Canada and Europe were enrolled. Clinical, ECG, exercise, cardiac magnetic resonance (CMR) and outcome data were analysed.ResultsOf the 873 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
228
3
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 413 publications
(253 citation statements)
references
References 27 publications
17
228
3
5
Order By: Relevance
“…Ratio ≥ 0.3 of RV mass-to-volume for rTOF patients was sufficient to reach high risk regarding adverse outcomes (HR 5.04, 95% CI 2.3-11.0, p < 0.001) [26]. Additionally, LV and/or RV dysfunction and documented atrial tachyarrhythmia may independently increase the probability of life-threatening outcomes.…”
Section: Right Ventricular Hypertrophymentioning
confidence: 95%
See 1 more Smart Citation
“…Ratio ≥ 0.3 of RV mass-to-volume for rTOF patients was sufficient to reach high risk regarding adverse outcomes (HR 5.04, 95% CI 2.3-11.0, p < 0.001) [26]. Additionally, LV and/or RV dysfunction and documented atrial tachyarrhythmia may independently increase the probability of life-threatening outcomes.…”
Section: Right Ventricular Hypertrophymentioning
confidence: 95%
“…Presence of documented atrial arrhythmias (described as atrial flutter, AF or SVT) in rTOF patients plays a predictive role in risk stratification for VT and SCD (HR 3.65 (95% CI 1.75-7.62, p = 0.001)) [26]. Echocardiography-based study found that most of undocumented arrhythmias were likely to be supraventricular and linked to increased right atrial (RA) size [27].…”
Section: Supraventricular Arrhythmiasmentioning
confidence: 99%
“…Other suggested risk factors that may not be as strongly associated with SCD include older age (after the first decade of life) at the time of complete repair, a history of syncope or rapid palpitations, extensive right ventricular fibrosis on cardiac magnetic resonance imaging (MRI) scan, elevated left ventricular end diastolic pressure, non-sustained VT on ambulatory cardiac monitor, and atrial arrhythmias. 16,18,[20][21][22][23] The presence of a single risk predictor portends only moderate risk of SCD. 20 In patients with moderate risk (ie, the presence of a single risk factor, symptoms suggestive of VAs without ambulatory monitor documentation), inducible VA at electrophysiology study (EPS) is considered to be predictive of clinical malignant arrhythmias.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…16,18,[20][21][22][23] The presence of a single risk predictor portends only moderate risk of SCD. 20 In patients with moderate risk (ie, the presence of a single risk factor, symptoms suggestive of VAs without ambulatory monitor documentation), inducible VA at electrophysiology study (EPS) is considered to be predictive of clinical malignant arrhythmias. EPS does not, however, predict adverse events in asymptomatic patients without risk factors.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…[1][2][3] However, early identification and characterization of a poorly adapting RV, and consequently RV failure, continues to be difficult.…”
Section: Introductionmentioning
confidence: 99%